Nonpharmacological Management of Diabetic Foot Ulcers: An Update. (September 2021) - Eleftheriadou, Ioanna; Samakidou, Georgia; Tentolouris, Anastasios; Papanas, Nikolaos; Tentolouris, Nikolaos
Diabetic foot ulcers (DFUs) are a common and serious complication of diabetes mellitus that is associated with increased morbidity and mortality, as well as substantial economic burden for the health care system. The standard of care for DFUs includes pressure off-loading, sharp debridement, and wound moisture balance, along with infection control and management of peripheral arterial disease. A variety of advanced modalities that target distinct pathophysiological aspects of impaired wound healing in diabetes are being studied as possible adjunct therapies for difficult to heal ulcers. These modalities include growth factors, stem cells, cultured fibroblasts and keratinocytes, bioengineered skin substitutes, acellular bioproducts, human amniotic membranes, oxygen therapy, negative pressure wound therapy, and energy therapies. Additionally, the use of advanced biomaterials and gene delivery systems is being investigated as a method of effective delivery of substances to the wound bed. In the present narrative review, we outline the latest advances in the nonpharmacological management of DFUs and summarize the efficacy of various standard and advanced treatment modalities.